Old age and disability: Same or different for the purposes of human rights law? - Georgantzi, Nena (Aequitas)

(untitled) (Réseau international sur le Processus de production du handicap (RIPPH), 2023)
Ageing and disability are often conflated in theory and practice when old age is seen as synonym to physical and cognitive decline. But distinct policies, advocacy frames and movements have also led to the exclusion and discrimination of older people with disabilities, when older people are offered fewer and poorer services. In both cases, persistent stereotypes about older people’s abilities lead to the conclusion that there is not much that can be done to assist older people and to integrate them in the life of their communities. International human rights law also reflects age biases as it is at least partly based on a medical model that accepts old age impairments as natural and inevitable. This paper makes the case for a rights-based approach to ageing and argues that the intersection between old age and disability merits further consideration by international human rights law and practice.